1996
DOI: 10.1177/002221949602900610
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Traumatic Brain Injury

Abstract: Experiencing a brain injury is a traumatic event not only for the child who is directly affected, but also for his or her family system. Recently, attention has turned toward the potentially deleterious effects of having a child with a traumatic brain injury (TBI) on parents, siblings, and extended family members. Specifically, families of TBI survivors may suffer major psychological, financial, role, and relationship risks. Therefore, treating the child with a brain injury is only one component of a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Videoconferencing may be beneficial as parents would not require transport or childcare and could potentially avoid time taken from work to attend face-to-face therapy sessions [28]. Paediatric TBI causes a considerable degree of financial strain for families [29], and any method for alleviating this strain is worth investigating. Furthermore, the risk of sustaining a paediatric TBI is increased for those who live in remote areas [30], highlighting the need to increase access to interventions for those who live far from rehabilitative services.…”
Section: Introductionmentioning
confidence: 99%
“…Videoconferencing may be beneficial as parents would not require transport or childcare and could potentially avoid time taken from work to attend face-to-face therapy sessions [28]. Paediatric TBI causes a considerable degree of financial strain for families [29], and any method for alleviating this strain is worth investigating. Furthermore, the risk of sustaining a paediatric TBI is increased for those who live in remote areas [30], highlighting the need to increase access to interventions for those who live far from rehabilitative services.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Taylor et al (2001) found that child behavior problems 6 months postinjury predicted higher family burden and parent psychological distress at 12 months. Clinical observations indicate that families of children with TBI are more likely to experience strain in family roles, lack of social support outside of the family, and low levels of support or communication within the family (Brooks, 1991; Conoley & Sheridan, 1996; Waaland & Kreutzer, 1988). In addition, the transition from the hospital to the child’s home can become even more stressful if the family experiences challenges beyond the TBI (Semrud-Clikeman, 2010).…”
mentioning
confidence: 99%